A Quick Access to Structurally Diverse Triazoloquinazoline Heterocycles via the MIL-101(Cr)-Catalyzed One-Pot Multi-Component Reaction of a Series of Benzaldehydes, Dimedone, and 1H-1,2,4-Triazol-3-Amine Under Green Conditions - Shiri, Pezhman; Niknam, Esmaeil; Aboonajmi, Jasem; Khalafi-Nezhad, Ali; Amani, Ali Mohammad (Frontiers in Chemistry, 2022)
A one-pot multi‑component reaction of a variety of benzaldehydes, dimedone and 1H-1,2,4-triazol-3-amine for the efficient synthesis of quinazolinone derivatives under green conditions is reported. It was proved that MIL-101(Cr) could carry out successfully this multicomponent strategy to afford target products in high yields. The scope and limitation of this catalytic system concerning the aldehyde substrates were explored. Different aldehydes could be conveniently delivered to quinazolinones at room temperature with short reaction times in an atom-economy way. Notably, MIL-101(Cr) has been also characterized with different analytic methods such as FT-IR, SEM, and EDX. The outstanding benefits of this methodology are the availability of substrates, using green conditions, excellent functional group compatibility and reusability of catalyst, therefore providing easy access to a range of products of interest in organic and medicinal chemistry.